Basic biomechanics of spinal cord injury — How injuries happen in people and how animal models have informed our understanding. (April 2019) - Mattucci, Stephen; Speidel, Jason; Liu, Jie; Kwon, Brian K.; Tetzlaff, Wolfram; Oxland, Thomas R.
Abstract: The wide variability, or heterogeneity, in human spinal cord injury is due partially to biomechanical factors. This review summarizes our current knowledge surrounding the patterns of human spinal column injury and the biomechanical factors affecting injury. The biomechanics of human spinal injury is studied most frequently with human cadaveric models and the features of the two most common injury patterns, burst fracture and fracture dislocation, are outlined. The biology of spinal cord injury is typically studied with animal models and the effects of the most relevant biomechanical factors - injury mechanism, injury velocity, and residual compression, are described. Tissue damage patterns and behavioural outcomes following dislocation or distraction injury mechanisms differ from the more commonly used contusion mechanism. The velocity of injury affects spinal cord damage, principally in the white matter. Ongoing, or residual compression after the initial impact does affect spinal cord damage, but few models exist that replicate the clinical scenario. Future research should focus on the effects of these biomechanical factors in different preclinical animal models as recent data suggests that treatment outcomes may vary between models. Highlights: Biomechanical parameters of spinal cord injury contribute to heterogeneity of human injuries. No single injury model can represent the clinical heterogeneity. Clinically relevant biomechanical parameters are often not replicated in injury models. Further model development is needed to more closely represent human injuries.